ANALISIS SISA MAKANAN DAN BIAYA SISA MAKANAN LUNAK MAKAN MALAM PASIEN KELAS III DI RSUPN DR. CIPTO MANGUNKUSUMO - Maharani Kusuma Dewi; Kusharisupeni Djokosujono (Jurnal Gizi dan Pangan Soedirman, 2022)
Food waste is a measure to determine the quality of good nutrition services in hospitals. According to the Indonesian Ministry of Health (2013), the patient's leftover food should be ≤20%. In fact, food waste is more common in soft foods than regular foods. The remaining food makes the patient's nutritional needs are inadequate and loss for hospital. This study aims to analyze the factors of the occurrence of soft food waste and the lost cost in patients at RSUPN Dr. Cipto Mangunkusumo in 2019. Quantitative research method with a cross sectional approach. Samples were taken by purposive sampling. The research subjects were class III patients. Data were analyzed by chi square and descriptive analysis. Data was collected by questionnaire. Food waste was measured by the food weighting method. Food waste is high if >20%. The results showed that the leftover soft food at dinner was (66.2%). Factors related to food waste was the patient's disease (p=0.027). The most cost of leftovers is animal dishes. The average cost of leftover soft food is Rp 4,035.92/person or Rp 104,590,866.80/year which is quite detrimental to the hospital. Therefore, it is hoped that costs can be reduced to achieves optimal goals.